2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25673
|View full text |Cite
|
Sign up to set email alerts
|

Manipulatives in Engineering Statics: Supplementing Analytical Techniques with Physical Models

Abstract: In order to assist students, gain conceptual understanding of internal forces, a physical manipulative of a truss was developed in order to help students visualize, feel, and analyze the behavior of the material being manipulated. The purpose of this qualitative study was to understand how a physical manipulative of a truss contributed to the conceptual understanding of truss analysis in statics. In this study, six students were presented with a simple problem of a truss, where no measurements or numerical qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…The use of experiential learning in statics is not new. Other authors [2]- [6] have developed hands-on activities that range from a manipulative truss model to help students conceptualize truss analysis [5] to three-dimensional particle equilibrium using electronic load cells [6]. In this paper, we present some new hands-on activities and more importantly, present activities that allow the students to easily compare measured and calculated values.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The use of experiential learning in statics is not new. Other authors [2]- [6] have developed hands-on activities that range from a manipulative truss model to help students conceptualize truss analysis [5] to three-dimensional particle equilibrium using electronic load cells [6]. In this paper, we present some new hands-on activities and more importantly, present activities that allow the students to easily compare measured and calculated values.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The use of hands-on models and manipulatives in mechanics instruction is not new or novel. There is a consistent strain of this work dating back decades [5], [12], [13], [14], [15], [16], [17], [18], [19], that includes approaches specifically targeting students' understanding of support models [20]. The work by Steif and Dollár in particular serves as inspiration for our approach with its emphasis on using manipulatives to help students develop a tactile feel for forces, couples, and reactions [5], [12].…”
Section: Introductionmentioning
confidence: 84%
“…Physical models are widely regarded as a useful focal point for student engagement in active learning, an instructional strategy that leads to learning gains across STEM disciplines [4]. Several authors including [3], [5], [6], [7], [8], [9] have identified hands-on learning with physical models and manipulatives as a useful approach to address gaps in conceptual understanding and serve other purposes in the mechanics classroom. These authors cite the potential of manipulatives and modeling activities to help students feel and visualize force interactions, link theory to students' prior knowledge, practice with modeling assumptions, and provide context to develop other engineering skills such as design and measurement.…”
Section: Prior Workmentioning
confidence: 99%